PEMBUATAN BIOPELET DENGAN MESIN EXTRUDER BERBAHAN BAKU LIMBAH PENYULINGAN BUAH PALA - Ibrahim, Gusri Akhyar (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Lampung, 2024)
Fossil energy is running low, causing an increase in the selling price of fossil fuels. This causes the global community to become aware and consider using renewable fuels which are more environmentally friendly. Utilizing nutmeg refining waste into biopellets can be a solution for managing waste and producing alternative fuel. This research focuses on utilizing nutmeg refining waste into biopellets with a mixture of 0%, 3% and 5% tapioca flour using an extruder machine with engine rotation speeds of 1700 RPM and 2800 RPM. The aim of this research is to determine the composition of the adhesive mixture and the engine rotation speed to obtain optimal heating value. The materials in this research were solid waste from nutmeg distillation and tapioca as adhesive. Making biopellets uses 2 treatments, namely 3 variations of adhesive mixture (0 gram, 90 grams, 150 grams) and 2 variations of machine rotation speed (1700 RPM and 2800 RPM). Meanwhile, the tools used are a pellet printing machine, tachometer, digital balance and caloribomb. The results obtained from testing the calorific value in this study were sample A 5,094.27 cal/g, Sample B 5,603.14 cal/g, Sample C 5,346.24 cal/g, Sample D 5,604.85, Sample E 5,789.10 cal/g, Sample F 5,571.65. So it can be concluded that the addition of adhesive and the engine rotation speed on the extruder machine affect the heating value obtained. Keywords: Biopellets, Extruder Machine, Nutmeg Refining Waste, Calorific Value